A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini) - Zhu, Bingyue; Ji, Lanzhu; Bian, Dongju (Zootaxa, 2019)
Pelthydrus schoenmanni sp. nov. (Coleoptera: Hydrophilidae) belonging to the Pelthydrus jendeki species group is described from Yunnan Province, China. Like other species of genus, it is known from streams. A revised key to the Pelthydrus jendeki group, the description, and genital illustration of this species are provided.